Phytochemical Analysis and Hepatoprotective Effect of Stem Bark of Oroxylum indicum (L) Vent. on Carbon Tetrachloride Induced Hepatotoxicity in Rat - Panda, S.K. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTThe present study was carried out to screen and evaluate the hepatoprotective activity of bark extracts of Oroxylum indicum (L.) Hepatoprotective activities of petroleum ether, chloroform, Methanolic and aqueous extracts of.O .indicum were examined against carbon tetrachloride induced liver damage in mice using silymarin as control. The extracts were screened for alkaloids, steroids, proteins, flavanoids, saponins, mucilage, carbohydrates, tannins, glycoside. Enzyme activities of Serum Glutamate Oxaloacetate Transaminase (SGOT), Serum Glutamate Pyruvate Transaminase (SGPT) and Alkaline Phosphatase (ALP) were analyzed. Results indicate that alcoholi bark extracts of O .indicum had activity over carbon tetrachloride treatment as compared to control. Results of the present investigation confirm the traditional uses of this plant as a potential hepatoprotective agent. The statistical analysis was carried out using one way analysis of variance (ANOVA) followed by Dunnet’s t-test. P-values <0.05 were considered as significant.